2021
DOI: 10.1155/2021/9923331
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Role and Mechanism of Herbal Medicine in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a complex neurodegenerative disease, manifested by the progressive functional impairment of the midbrain nigral dopaminergic neurons. Due to the unclear underlying pathogenesis, disease-modifying drugs for PD remain elusive. In Asia, such as in China and India, herbal medicines have been used in the treatment of neurodegenerative disease for thousands of years, which recently attracted considerable attention because of the development of curative drugs for PD. In this review, we fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 222 publications
(273 reference statements)
0
11
0
Order By: Relevance
“…Herbal medicines, including extracts from Ginkgo biloba extract (GBE), have gradually come to attention as novel therapies for PD. Herbal medicines generally share the advantages of multilevel functions with fewer adverse effects ( Yin et al, 2021 ). Among the most frequently applied herbal medicines, GBE has been used in clinical therapies since the early 1970s ( Saponaro et al, 1971 ; Bartolo, 1973 ).…”
Section: Introductionmentioning
confidence: 99%
“…Herbal medicines, including extracts from Ginkgo biloba extract (GBE), have gradually come to attention as novel therapies for PD. Herbal medicines generally share the advantages of multilevel functions with fewer adverse effects ( Yin et al, 2021 ). Among the most frequently applied herbal medicines, GBE has been used in clinical therapies since the early 1970s ( Saponaro et al, 1971 ; Bartolo, 1973 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of PD, some bioactive compounds have also been identified that could have a positive impact on the course of this disease. Thus, there is evidence demonstrating the antioxidant, anti-inflammatory, and therefore neuroprotective role of different herbs present in traditional Chinese and Indian medicine [ 171 ]. These effects are extensible to other types of molecules, such as the phenolic compounds present in many nutritional products (e.g., secoiridoids, phenolic alcohols, phenolic acids, flavonoids, and lignans).…”
Section: Resultsmentioning
confidence: 99%
“…Some in vivo and in vitro studies have proved their ability to increase the mRNA expression of stress‐responsive genes and reduce the expression of inflammatory mediators. (De Oliveria et al, 2009; Martins et al, 2016; Rahman et al, 2021; Yin et al, 2021).…”
Section: Phytotherapy For Neurodegenerative Dementiasmentioning
confidence: 99%